2019
DOI: 10.21273/hortsci13871-19
|View full text |Cite
|
Sign up to set email alerts
|

Pepper Photosynthesis, Stomatal Conductance, Transpiration, and Water Use Efficiency Differ with Variety, Indigenous Habitat, and Species of Origin

Abstract: The instantaneous photosynthetic rate (Pn), transpiration rate (E), and stomatal conductance (gS) were measured for 33 outdoor-grown Capsicum varieties (varying in species of origin and indigenous habitat) between 29 July and 22 Aug. 2017 using a portable gas exchange meter. Cuvette leaf temperature (Tleaf) and relative humidity (RH) were recorded at that same time. Pn Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
2
1
0
4
Order By: Relevance
“…Some genotypes may yield enormous, heavy fruits, whereas others may produce smaller, lighter fruits. This variation is in conformity with the value of Usman et al (2014), Bundela et al (2017), Ridzuan et al (2019), and Erwin et al (2019). Among all the chili genotypes, Putra Chili 1 gave the highest photosynthesis rate (15.04 µmol CO2 m -2 s -1 ) while AVVPO702 gave the lowest rate (9.79 µmol CO2 m -2 s -1 ) which were followed by genotypes DP-57 (9.79 µmol CO2 m -2 s -1 ), AP-18 (9.79 µmol CO2 m -2 s -1 ), Control 1 (9.81 µmol CO2 m -2 s -1 ) and Control 2 (10.16 µmol CO2 m -2 s -1 ), respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Some genotypes may yield enormous, heavy fruits, whereas others may produce smaller, lighter fruits. This variation is in conformity with the value of Usman et al (2014), Bundela et al (2017), Ridzuan et al (2019), and Erwin et al (2019). Among all the chili genotypes, Putra Chili 1 gave the highest photosynthesis rate (15.04 µmol CO2 m -2 s -1 ) while AVVPO702 gave the lowest rate (9.79 µmol CO2 m -2 s -1 ) which were followed by genotypes DP-57 (9.79 µmol CO2 m -2 s -1 ), AP-18 (9.79 µmol CO2 m -2 s -1 ), Control 1 (9.81 µmol CO2 m -2 s -1 ) and Control 2 (10.16 µmol CO2 m -2 s -1 ), respectively.…”
Section: Resultssupporting
confidence: 90%
“…Third highest fruit yield was recorded by cluster VI (648.95 g). Similar cluster distance analysis was found by many investigators and chili genotypes were grouped based on the morphological, physiological and yield traits and also genetic divergences were reported on chili genotypes and research suggest that genotypes with the best performance may be adopted in future breeding program (Usman et al, 2014;Meena et al, 2016;Erwin et al, 2019;Ridzuan et al, 2019).…”
Section: Cluster Analysis Of Selected Chili Genotypessupporting
confidence: 78%
“…They reported that increasing salinity level and water deficit caused reductions in WP, but they did not report varietal differences. Varietal differences in WPs were reported for different water regimes such as for wheat van den Boogard et al (1997); for peanut Bhatnagar-Mathur et al (2007), Ratnakumar et al (2009) and Devi et al (2009); for pepper Erwin et al (2019). Erwin et al (2019) stated that differences in water use properties among pepper varieties are higher than previously reported.…”
Section: Water Use and Productivitymentioning
confidence: 92%
“…A növények termőképességét alapvetően az elsődleges anyagcsere folyamatok és ezen belül is döntően a fotoszintézis teljesítménye határozza meg [1,3,6,8]. A világon a legnagyobb, míg Magyarországon a második legnagyobb felületen hajtatott zöldségfaj a paradicsom.…”
Section: Bevezetésunclassified